Adopting an Ecological Health Model to Harmful Alcohol Use in Nigeria’s Niger Delta - Agwu, Prince; Okoye, Uzoma; Ebimgbo, Samuel; Agbawodikeizu, Uju; Ijeoma, Igwe (European Journal of Mental Health, 2018)
Substance abuse has ravaged potentials and keeps clamping down on the stability of societies. It is increasingly becoming a social problem that demands sustainable remedies, particularly in Nigeria’s Niger Delta. This paper establishes a case for the utilisation of an ecological health model in dealing with harmful alcohol use in the region. What motivates the adoption of such a model is the fact that harmful alcohol use largely stems from nurture and can be remedied through same nurture. This paper adopted a case study research design using participant observation for data gathering, while using thematic analysis in organising and interpreting data.